INDUKSI PERKECAMBAHAN BENIH SIRSAK (Annona muricata L.) DENGAN PERLAKUAN SKARIFIKASI DAN KNO3 - Titin, Titin; Tambing, Yohanes; Ramli, Ramli (AGROTEKBIS, 2018)
Soursop (Annona muricata L.) were from North America and spread to the tropics and is one of the fruits with varying properties, ranging from fulfillment source of vitamins and minerals to play a role in the health field. Soursop production in Indonesia is low because not many farmers interested in cultivating remedy because the limitaion in the nursery. One of the obstacles in the nursery soursop is not immediately germinate seeds (dormant), because the seed soursop has a thick skin and hard that is impermeable to water and gases that in hibit germination. The purpose of this study is to determine the effect of scarification and KNO3 to induce germination of seeds of soursop. This research was conducted in March-May 2015, at the Laboratory of BKU Horticulture, Faculty of Agriculture, University of Tadulako. This research method using a completely randomized design (CRD) using two-factor treatment, while treatment factors as follows: The first factor is scarification: scarification by removing the skin at the tip of the seed, scarification with sanding one side of the seed, scarification with sanding two sides seed, second factor is the immersion of KNO 3: concentrations of 0.2% KNO 3, KNO 3 concentration of 0.4%, 0.6% KNO3 concentration, concentration of 0.8% KNO 3, obtained: 12 treatment combinations, each combination is repeated three times so there are 36 experimental units. The results showed that interaction scarification and KNO3 treatment significantly affect the germinationand time to germinate. Scarification treatment with sanding one side of the seed and the concentration of 0.4% KNO3 promote better germination based on the germination rate (91.11%)and time to germinate (5.69 days). Keywords: Dormancy, Potassium nitrate, Scarification, Soursop seed.